Experimental investigation of RC beam-slab substructures against progressive collapse subject to an edge-column-removal scenario - Lu, Xinzheng; Lin, Kaiqi; Li, Yi; Guan, Hong; Ren, Peiqi; Zhou, Yulong (Engineering structures, 2017)
•Five substructure specimens are tested under an edge-column-removal scenario.•Collapse mechanism is studied through material strain and structural responses.•Effects of various structural parameters on the collapse resistance are studied. When a reinforced concrete (RC) frame subjected to an edge-column-removal scenario, its floor system exhibits a complicated mechanism against progressive collapse due to the interaction between beams and slabs and the two-way load transfer characteristics. In this study, laboratory tests of five 1/3-scaled RC frame substructure specimens, including four beam-slab specimens and one beam specimen without a slab, are reported. The effect of critical structural parameters (i.e., the beam height, slab thickness and seismic reinforcement) on the collapse resistance was investigated by analyzing the applied loads, structural deformations and material strains. The RC slabs contribute to an increased collapse resistance of the control beam-slab specimen by 146% under small deformations (i.e., the beam mechanism) and 98% under large deformations (i.e., the catenary mechanism) compared to the beam specimen. The resistances of the beam-slab specimens were mainly provided by the slabs and the beams in the direction along the free edge, more significantly by the portion close to this edge where the largest deformation was developed. Increasing the seismic reinforcement in the beams resulted in a much larger collapse resistance under both beam and catenary mechanisms. In contrast, increasing the slab reinforcement by expanding the slab thickness marginally improved the collapse resistance under the catenary mechanism but contributed little to that under the beam mechanism. Increasing the beam height also largely improved the collapse resistance under the beam mechanism, but had limited impact to that under the catenary mechanism.